Efficiency Estimation of Synchronous Generators for Marine Applications and Verification With Shop Trial Data and Real Ship Operation Data - Hiroyasu Kifune; Mehdi Karbalaye Zadhe; Hidetsugu Sasaki (IEEE Access, 2020)
Three methods were explored to estimate the efficiency for the conversion of mechanical power to electrical power using synchronous generators in ships at low power factors. Generally, the generator efficiency data is provided by manufacturers as shop trial data and is measured by operating generators under power factor of 0.8 and 1.0. However, the efficiency of synchronous generators is not measured under low power factor of less than 0.8. In practice, onboard generators occasionally operate at low power factor and it is desirable to clarify their characteristics for power system designers of large vessels. By substituting the shop trial data into the proposed efficiency estimation formulas, the generator efficiency at low power factor was extrapolated. To evaluate the validity of these methods, the fuel consumption characteristics of diesel engines as prime movers was focused. The estimation of the generator efficiency was indirectly validated using a statistical analysis of long-term observational data of the generator in operation. As a result, the efficiency estimation method based on a power loss mechanism gave the most reliable result among the three estimation methods. The root mean squared error of the calculated specific fuel consumption was 3.5 g/kWh, which is approximately 1.66 % error rate.